La sombra de Pachacamac: Huari en la costa central - Kaulicke, Peter (Pontificia Universidad Católica del Perú, 2012)
Pachacamac's Shadow: Huari on the Central CoastThis paper presents the material evidence from the Middle Horizon on Peru's Central Coast, as well as the situation immediately preceeding its beginnings. Concepts of style as well as spatial contextualization in settlements and burial areas are defined and discussed in order to define social identities and sociopolitical situations that help understand regional changes against a greater background. Principal topics are the specific character of Lima urbanism, social and spatial reconstructions of Nievería and Pachacamac, and contacts with the north central and north coast, as well as the adjoining highlands to the east. These highlands form a vital corridor into the interandean valleys and they were the stage for dynamic conflicts between coastal and highland polities. On the basis of current knowledge it appears that Huari did not adopt highly aggressive means of control such as direct colonization. Quite the contrary, independence and the persistence of local and regional identities co-existed within an atmosphere of "international" relations that imply social complexity that is not yet understood. More investigations must be directed at specific social conditions before alternative hypotheses about general social context can be formulated.